Liquid crystal anchoring transitions and weak anchoring interface formation at surfaces created by uniquely designed acrylate copolymers. (5th May 2017) - Rijeesh, K.; Higuchi, Hiroki; Okumura, Yasushi; Yamamoto, Jun; Kikuchi, Hirotsugu
Abstract: Weak anchoring of liquid crystals (LCs) can, in principle, have the potential to provide lower operating voltage systems with an improved electro-optic response. The creation of such a liquid crystal system is an important goal for next-generation displays, including polymer-stabilized blue phases. Herein, we report a new method of weak anchoring for LCs in contact with uniquely designed amorphous side-chain copolymers that feature both mesogenic and non-mesogenic units. The mesogenic pendant enhances the compatibility with the LC molecules, while the non-mesogenic part reduces the possible azimuthal anchoring energy of the mesogenic side-chain on LCs. The copolymers with mesogenic pendants bearing polar and non-polar end groups favor planar and homeotropic alignments, respectively. Interestingly, LCs in a glass plate cell coated with these side-chain non-liquid crystalline copolymers showed anchoring transitions and weak anchoring interface formation at precise temperatures. The weak anchoring nature of LCs on copolymer surfaces was confirmed by their easy response to an applied magnetic field. These results suggest that the copolymers perform an important function as weak anchoring surfaces for nematic LCs. Graphical abstract: Highlights: Side-chain non-liquid crystalline polymers (SNLCP) bearing mesogenic moieties were designed and synthesized. Different LC alignments were observed for SNLCP with a polar end group (planar) and non-polar end group (homeotropic). LC molecules in contact with SNLCP showed anchoring transitions and weak anchoring interface formation. A new approach to weak anchoring of nematic LCs with a control over initial alignment was successfully demonstrated.